Current distribution characteristics of trace elements in the coral-reef systems of Xisha Islands, China. (January 2020) - Li, Jingxi; Sun, Chengjun; Zhang, Letian; Ding, Jinfeng; Jiang, Fenghua; Wang, Zongxing; Wang, Zhangyi; Fu, Liang
Abstract: The distribution characteristics, correlation, and bioavailability of 14 trace elements in different fishes and corals collected from the coral-reef systems of the Xisha Islands, China were systematic studied for the first time. All detected elements were measured using inductively coupled plasma mass spectrometry after pretreatment by microwave digestion. The fishes had slight differences in element enrichment selectivity and bioavailability with average levels as follows: V, 0.100 mg·kg −1 ; Cr, 0.683 mg·kg −1 ; Mn, 1.178 mg·kg −1 ; Fe, 51.806 mg·kg −1 ; Co, 0.072 mg·kg −1 ; Ni, 1.286 mg·kg −1 ; Cu, 1.428 mg·kg −1 ; Zn, 10.384 mg·kg −1 ; As, 6.437 mg·kg −1 ; Se, 0.830 mg·kg −1 ; Mo, 0.101 mg·kg −1 ; Cd, 0.051 mg·kg −1 ; Pb, 0.308 mg·kg −1 ; and U, 0.008 mg·kg −1 . Trace element contents in corals were higher than those in fishes. The distribution characteristics of trace elements in fishes and corals presented a significant correlation in North Reef and Yongle Atoll, thereby indicating an evident effect on living areas compared with trace elements in fishes from the Spratly Islands. Cluster analysis of fishes and corals based on trace elements showed that they had different selectivities and bioavailabilities to trace elements. The EDI and THQ ratios of Cu, As, Cd, Cr, and Pb demonstrated that fishes were unlikely to experience serious adverse effects, except for As in Chaetodon auriga, Myripristis kuntee, Gnathodentex aureolineatus, and Hemigymnus melapterus in Xisha Islands. Highlights: Trace elements in fishes and corals presented a significant correlation. Fishes and corals showed different bioavailabilities to trace elements. Significant distribution trend of trace elements were found in the coral systems.